Teks Pada Batu Nisan Baron Van Imhoff Dilihat Melalui Analisis Semiosis Model Peirce dan Danesi-Perron - Suratminto, Lilie (Makara Human Behavior Studies in Asia, 2007)
Entering the Puppet Museum in Jakarta we come across with beautiful tombstones of the period of The Dutch –East Indian Company or the VOC (Verenigde Oost Indische Compagnie). The tombstones are clinking on the left wall inside the building. Compare with the others, the tombstone of Gustaaff Willem Baron van Imhoff is very unique because it has a different style of its heraldry. This paper revealed the historical background of Van Imhoff who had played an important role in the Indonesian’s colonial history in the middle of the eighteen century. The micro and the macro analyses of the data of the tombstone show that the verbal and the non-verbal data support the historical data. The result of this analysis enriches the knowledge of the cultural heritages from the colonial period of our country.